Hercules full circle ebook - Layton, Bob (Hercules: Full Circle., 2018)
Collects Marvel Tales (1966) #197, Marvel Graphic Novel #37 and material from Marvel Comics Presents (1988) #39-41 & Marvel Age #4 & #65. Bob Layton had a vision of the future - Greek gods, sarcastic robots, transvestite aliens and more - and it's time to share it! The Prince of Power encounters the Wonder of the World of Wilamean, his own half-human son! Can the man-god who changed the courses of rivers and history steer his son to the path of justice? It'll help that there's a lot of fighting involved!